The - Porter, Burton F. (Oxford University Press, 2002)
Lively, comprehensive, and contemporary, The Voice of Reason: Fundamentals of Critical Thinking covers three principal areas: thought and language, systematic reasoning, and modes of proof. It employs highly accessible explanations and a multitude of examples drawn from social issues and various academic fields, showing students and other readers how to construct and criticize arguments using the techniques of sound reasoning...